EFEKTIVITAS PROGRAM APLIKASI SIPRAJA DALAM PELAYANAN ADMINISTRASI BERBASIS DIGITAL DI DESA KARANGTANJUNG KECAMATAN CANDI KABUPATEN SIDOARJO - Dini Ananda Nur Amalia; Isnaini Rodiyah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
This research aims to analyze and describe the effectiveness of the SIPRAJA application program in digital-based administrative services in Karang Tanjung village, Candi District, Sidoarjo Regency. This research uses a qualitative descriptive method with a technique for determining informants called purposive sampling. The informants who were used as research subjects consisted of the Village Secretary and the Head of the Community and Services Section. Data collection was carried out through interviews, observation and documentation. The method used in this research is descriptive qualitative with a technique for determining informants, namely purposive sampling. The informants in this research were the Village Secretary, Head of the Services and Community Section. Data collection techniques can be obtained through interviews, observation and documentation. The data analysis in this research uses Milles and Huberman's theory, namely data collection, data reduction, data presentation, and drawing conclusions and verification. The research results show that the SIPRAJA Application is said to be not yet effective for the Karang Tanjung Village Community where there is a difference between online and offline applications via the SIPRAJA Application. There is only one human resource as operator, namely the Village secretary and the village head as application verifier. Then the community does not incur any costs for this program, and the community can use the facilities and infrastructure provided at Kanto Village. The number and quality of services are effective, handling each administrative service at SIPRAJA only takes 5-10 minutes. Regarding the service procedures, they are good and correct, but people who still don't understand technology choose to submit administrative applications offline to the Karang Tanjung Village Office.